Schooling impacts of an unconditional cash transfer program in Mali - Sessou, Eric; Hidrobo, Melissa; Roy, Shalini; Huybregts, Lieven (International Food Policy Research Institute, 2022)
In rural West Africa, the rate of out-of-school children is high and delayed entry to primary school is common, particularly for girls. Using the randomized roll-out of an unconditional cash transfer program (Jigisemejiri) in Mali, we examine its impact on child schooling by age and sex. The program leads to significant improvements in schooling outcomes for girls, but not boys. Improvements among girls are especially salient among younger (ages 6–9) and older (ages 15–18) girls. Pathway analysis reveals that the program reduces the time younger girls spend in agricultural work at home and the time older girls spend in domestic work as well as self-employment. Households in the program also spend more on education for older girls in terms of school fees, materials, and transport.